AB0389 The immunogenicity of branded and biosimilar infliximab in rheumatoid arthritis according to th9-related responses. (15th June 2017) - Talotta, R; Berzi, A; Doria, A; Batticciotto, A; Ditto, MC; Trabattoni, D; Puttini, P Sarzi
Abstract : Background: There are many evidences that Th9 lymphocytes take part to the pathogenesis of rheumatoid arthritis (RA), however it is unclear whether these cells are implicated in the immunogenicity of biologic agents. Objectives: We aimed to evaluate the immunogenicity of branded and biosimilar infliximab by detecting changes in Th9 percentages following an "in vitro" stimulation test. Methods: PBMCs from 55 consecutive RA outpatients (15 drug-free, 20 successfully treated with branded infliximab and 20 failing branded infliximab) and from 10 healthy controls were collected. PBMCs were cultured with/without 50 μg/mL infliximab originator (Remicade®) or 50 μg/mL infliximab biosimilar (Remsima®), 50 μg/mL Human IgG1kappa and 50 μg/mL recombinant Human IgG Fc for 18 hours. Th9 lymphocytes were identified by means of flow cytometry as PU.1+, IRF4+, IL9+ CD4+ cells. Furthermore, the markers CCR7 and CD45RA were used to distinguish naive from memory IL-9-producer cells. Results: In unstimulated condition, RA patients showed the highest percentages of Th9 lymphocytes. Following stimulation with branded infliximab, the percentage of PU.1+, IRF4+ Th9 cells, CCR7+, CD45RA- central memory and CCR7-, CD45RA- effector memory IL-9 producer cells significantly increased in the group of infliximab non responder RA patients. On the contrary, no significant variation was observed after biosimilar exposure. Figures 1, 2, 3, 4 resume the results. Conclusions: According to our results, Th9 cells seem to be involved in the immune response against the epitopes of branded but not biosimilar infliximab and this condition could rely on the recall and the stimulation of both central and effector memory cells. Further studies are indeed needed to confirm these data. Disclosure of Interest: None declared